Desenvolvimento e caracterização de hidrogéis de gelatina/tanino amino-funcionalizado para aplicações como suportes porosos na área biomédica - Bezerra, Ewerton de Oliveira Teotônio (2019)
This work proposes for the first time the preparation of physical hydrogels based on gelatin (GE) and an amino-functionalized condensed tannin derivative (commercially called tanfloc; TN). Firstly, before preparing the hydrogels, TN solution (5% w/v) was purified by the dialysis process (5 days). It has been found that TN is primarily formed by oligomers (molar weight < 12 kDa). It was also confirmed by means of scanning electron microscopy (SEM), coupled to an X-ray dispersive energy detector (EDS), infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS), that the as-received TN presents chloride, calcium and potassium ions as impurities in its composition. The structure of the commercial TN is compact, organized and spherical, whereas the purified TN shows a brittle structure without organization. The dialyzed TN solution was used to prepare the GE/TN hydrogels. Aqueous solutions of GE and TN were mixed (50 °C) to design stable blends. Then, GE/TN blends were conditioned at 4 °C (24 h). Afterward, thermosensitive GE/TN hydrogels were obtained for the first time, being the gelling temperatures of the hydrogels determined by measurements of the storage modulus (G') as a function of the temperature. GE/TN hydrogels were characterized by rheological tests, FTIR, XPS and SEM. Rheological tests revealed that the hydrogels had a sol-gel temperature above the human body temperature (37 °C). SEM images showed a morphology with interconnected pores, which are irregularly distributed on the hydrogel surfaces. The GE90/TN10 sample (formed from a blend composed of 90 vol% GE (4.0% w/v) and 10 vol% TN) showed antimicrobial activity against Escherichia coli (E. coli) due to the diffusion of TN in the culture plate seeded with the bacterium, while the GE50/TN50 sample (formed from a blend composed of 50 vol% GE (4.0% w/v) and 50 vol% TN) showed no inhibition halo against E. coli. This effect is due to the greater stability of the GE50/TN50 hydrogel in PBS solution for up to 7 days. Because of this property, this physical hydrogel was applied as a scaffold matrix to promote adhesion and proliferation of bone mesenchymal stem cells (BMSCs). The GE50/TN50 hydrogel presented cytocompatibility with BMSCs. Furthermore, fluorescence and SEM images revealed that the GE50/TN50 hydrogel acted as scaffold, because within 7 days the matrix promoted fixation, proliferation and spreading of BMSCs on its surface. This material based on GE and TN presents can have a potential application in the tissue engineering field, acting as a scaffold matrix.